Strategi Governance Melalui Community Based Tourism Sebagai Upaya Penyelesaian Konflik Wisata di Gua Pindul - Akbar Farid; Muhammad Amri; Muhammad Fahry; Muhammad Fuad (Politicos: Jurnal Politik Dan Pemerintahan, 2022)
This study aims to look at the roots of conflict in the Pindul Cave tourist area and see what potentials are likely to be intervened using conflict management governance practices. This study also recommends the concept of Community-Based Tourism that can be applied to Pindul Cave tourism as an effort to resolve conflicts. This study uses a qualitative method. Based on the research results, there is a land conflict between Atik Damayanti as the owner of part of the land in Pindul Cave Tourism and Pokdarwis in Bejiharjo Village, Gunungkidul Regency and BUMDes, Bejiharjo Village, Gunungkidul Regency. Second, is the conflict in the management of Pindul Cave tourism which has 11 Pokdarwis competing with each other, resulting in several jockeys and marketing playing the price of tourism in Pindul Cave. Other results include examples of the implementation of Community-Based Tourism that can be realized in the Pindul Cave Tourism Village, Bejiharjo Village, and Gunungkidul Regency as an effort to practice governance in conflict resolution.